Importance of teakwood extractives on wood properties and for tree breeding. - H Simatupang, Maruli (1995)
Teak is indigenous in India, Myanmar, and Thailand, but is currently cultivated in many parts of the world. Teakwood is one of the oldest commercial wood species.